Characteristics of Lactobacillus plantarum QZW5 and its effects on wheat silage under multigelation - Miao Zhang; Guofang Wu; Lei Wang; Bei Zhang; Jun Chen; Yuan Liu; Huili Pang; Zhongfang Tan (Chemical and Biological Technologies in Agriculture, 2021)
Abstract Background Silages, as a nutritious and long-term preserved fodder, is achieved through fermentation. However, the constant low temperatures and freeze–thaw event are key factors that affect the quality of silages due to low levels of lactic acid production and undesirable microbial community revitalization. In this study, we attempt to investigate the effects of Lactobacillus plantarum QZW5 on the fermentation characteristics of wheat silage under ensiling conditions at the order of the following temperatures: constant low temperatures (5 °C for 30 days), multigelation (10 ℃ at day and – 10 ℃ at night for 30 days) and room temperature (aerobic/anaerobic, 10 days). Results Under multigelation condition, Lactobacillus plantarum QZW5 inoculation significantly increased the contents of lactic acid and acetic (P < 0.05) in the silage. The pH, bacterial richness index (Chao) and diversity index (Shannon) of the silage were significantly decreased by Lactobacillus plantarum QZW5 (P < 0.05). In Lactobacillus plantarum QZW5 inoculated silage, the dominant genera were L. plantarum subsp. plantarum. However, those in the control silage were Leuconostoc mesenteroides and Leuconostoc fallax. LAB (lactic acid bacteria) inoculation increased the abundance of desirable Lactobacillus spp. and inhibited the growth of undesirable Escherichia coli, Saccharomyces cerevisiae, and Filamentous fungi, among others in the silage. Conclusions Therefore, inoculation of L. plantarum QZW5 during ensiling could stimulate favorable fermentation and reconstruct bacterial community for better silage preservation. Graphic abstract